Jamaica : Sixth Review Under the Arrangement Under the Extended Fund Facility. (IMF Staff Country Reports; Country Report, 2014)
Discussions centered on the preparations for the 2015/16 budget, and reforms to strengthen the financial sector and boost growth. The authorities have deepened their efforts in supporting their ambitious fiscal goals by strengthening public financial management and revenue administration, and they reiterated their resolve to continue containing the wage bill. Steps have also been identified to advance the reform of the securities dealers and to increase the resilience of the financial system.